Trekking Use Pattern and Perception of Users and Residents Towards Trekking Tourism in the Annapurna Sanctuary Trail, Nepal - K. Shrestha, Suresh (1993)
The study assesses trekking use pattern and perception of trekkers and residents towards trekking tourism in the Annapurna Sanctuary Trail (AST) which is one of the most popular trekking areas in Nepal. Two separate questionnaire surveys, one representing 135 randomly selected trekkers and another involving 110 randomly selected households were conducted. The overall perception of trekkers was measured by a composite index developed from their opinions for six different attributes of the journey in the AST, where 1 represented most favourable perception and 4 represented most unfavourable perception. Likewise, residents' opinions on support for tourism, perception towards tourism's impacts and opinions for progressive tourism management statements were used in measuring the overall perception of residents, but in this case I represented most negative perception while 4 denoted most positive perception. It was found that the characteristics of the trekkers and pattern of use of the AST were not much different from other wilderness areas in the world. The per day expenditures of the trekkers in the AST was NRs . 222.2. They also spent large sum of money on trekking fees and porters and guides. However, this money is not retained in the area. Although the trekkers expressed somewhat unfavourable views towards litter condition and a few services, they in general showed positive view towards all attributes of the journey in the AST. It was noted that there were significant differences in the perceptions of trekkers towards various attributes of the journey in the AST; and area features was the most important factor in explaining the perception of journey in the AST.